EXPRESSIONS OF APPRAISAL SYSTEMS ON STUDENT-TEACHER INTERACTION IN EFL CLASS - Herdiawan, Rama Dwika; Nurhidayat, Eka Nurhidayat; Yuliana, Nanda Yuliana (Universitas Teknokrat Indonesia, 2024)
This study explores the role of appraisal systems within student-teacher interactions in English as a Foreign Language (EFL) classrooms, focusing on how these linguistic resources shape the educational experience. Utilizing a qualitative case study approach, data were collected through classroom observations, audio recordings, and semi-structured interviews with EFL teachers and students in Majalengka. The analysis, grounded in Systemic Functional Linguistics, identified key patterns in the use of appraisal language, including expressions of attitude, engagement strategies, and graduation. The findings reveal that positive appraisals significantly enhance student engagement and motivation, while the strategic use of engagement and graduation in feedback helps create an inclusive and supportive learning environment. Teachers' positive attitudes and validation of students' contributions foster a sense of belonging and confidence among learners. Conversely, negative appraisals, though less frequent, can adversely affect student morale and participation. This research highlights the critical role of nuanced and supportive communication in EFL education. It offers practical insights for educators to refine their interactional strategies, emphasizing the importance of positive reinforcement, inclusive engagement, and calibrated feedback. The study underscores the need for further research to explore appraisal systems in diverse educational settings and their long-term impact on student outcomes. By bridging the gap between linguistic theory and educational practice, this study aims to contribute to the enhancement of pedagogical approaches in EFL classrooms.